2021
DOI: 10.1002/adfm.202101163
|View full text |Cite
|
Sign up to set email alerts
|

Benzylammonium‐Mediated Formamidinium Lead Iodide Perovskite Phase Stabilization for Photovoltaics

Abstract: There is an ongoing surge of interest in the use of formamidinium (FA) lead iodide perovskites in photovoltaics due to their exceptional optoelectronic properties. However, thermodynamic instability of the desired cubic perovskite (α-FAPbI 3 ) phase at ambient conditions leads to the formation of a yellow non-perovskite (δ-FAPbI 3 ) phase that compromises its utility. A stable α-FAPbI 3 perovskite phase is achieved by employing benzylammonium iodide (BzI) and the microscopic structure is elucidated by using so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…Moreover, the structure of PbI 2 almost completely followed the structure and orientation of the surrounding perovskite, making PbI 2 a possible seed for perovskite growth, as shown in Figure 3B. [49] Seol et al found that dropping the concentration of FAI from 58.2 to 40.7 mM in the two-step 2021 [100] ITO/SnO 2021 [121] FTO/TiO and 90% initial PCE after 500 h [11] ITO/NiOx/FAPbI The color of modified perovskite films appear dark after 5 weeks in ambient. [99] method could increase the surface roughness and grain size of the FAPbI 3 film.…”
Section: Precursor Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the structure of PbI 2 almost completely followed the structure and orientation of the surrounding perovskite, making PbI 2 a possible seed for perovskite growth, as shown in Figure 3B. [49] Seol et al found that dropping the concentration of FAI from 58.2 to 40.7 mM in the two-step 2021 [100] ITO/SnO 2021 [121] FTO/TiO and 90% initial PCE after 500 h [11] ITO/NiOx/FAPbI The color of modified perovskite films appear dark after 5 weeks in ambient. [99] method could increase the surface roughness and grain size of the FAPbI 3 film.…”
Section: Precursor Conditionsmentioning
confidence: 95%
“…Furthermore, with the bulk organic cations or low-dimensional perovskite assembled at the GB, high-efficiency mesoporous FAPbI 3 PSCs had been obtained. [25,[99][100][101] Especially, FAPbI 3 PSCs based on the mesoporous structure with the carbon electrode was also obtained by the printable fabrication process, which was reported to present a stability of 288 h in ambient with the 50-70% RH without encapsulation, as shown in Figure 9C. [101,102] The inverted p-i-n structure is considered to be easier to achieve robust stability due to the removal of 2 0 , 7, 7 0 -tetra-(dimethoxydiphenylamine)-spirofluorene (Spiro-OMeTAD).…”
Section: Optimization Of Device Structure and Interface Layersmentioning
confidence: 99%
“…Long‐chain organic ammonium for the surface functionalization of 3D FAPbI 3 perovskites has been demonstrated to effectively stabilize the metastable phase‐pure FAPbI 3 . [ 164 ] To uncover the mechanism of surface‐induced phase stabilization, various organic ammonium cations involving BA + , 4‐fluorophenylethylammonium (FPEA + ), and PEA + have been investigated using surface analysis and DFT calculation. [ 165 ] The theoretical analysis result confirms that organic ammonium functionalization enables reducing the surface energy of the perovskite phase and synergistic decrease in the nanocrystal size, realizing excellent optoelectronic properties.…”
Section: Multifunctional Materials For Optimizing Pure Fapbi3 Perovsk...mentioning
confidence: 99%
“…Sometimes, a reflection signal was not observed in the films containing FAI, suggesting the low-dimensional perovskite phases either do not form in the existence of FAI or are highly disordered, which prevents their detection. 35,36 The PbI 2 peak located at 12.68° in the sample may be ascribed to the degradation of perovskite materials caused by the escape of organic cations during the annealing procedure of the perovskite films, resulting in excessive PbI 2 being left in the perovskite precursors. 37 After the in situ crosslinking strategy, the peak intensity of PbI 2 is perceptibly reduced.…”
mentioning
confidence: 98%